Penggunaan teknik akrostik dalam pembelajaran menulis puisi di SMP - Siti Aisyah; Yusra D; Rahmawati Rahmawati (Universitas Lampung, 2023)
This research was conducted to describe the effectiveness of the use of the acrostic technique in teaching poetry writing at MTS Labor UIN STS Jambi. Issues in poetry writing at MTS Labor UIN STS Jambi can still be found, one of which is that students are not interested in writing poetry because it is difficult to determine the next word in writing poetry. The acrostic technique is a technique that makes it easier to write poetry. The method used was a quantitative type of quasi-experiment design with a one group pretest-posttest setting. Data analysis techniques used inferential statistics in the form of a t-test, preceded by a Homogeneity Test and a Normality Test. The results of the research showed a significant difference between the pretest and posttest results of students' poetry writing, where the significance value of the t-test obtained was 0.00, which was less than 0.05. This proves that the acrostic technique is effective in teaching poetry writing. Student difficulties in composing poetry can be overcome by using the acrostic technique. This research is limited by a short time. So it is hoped that future research can cnduct research with a longer time and combined with other learning models or approaches.Keywords: Effectiveness, Acrostic technique, poetry